Molecular Detection and Genotyping of Enterocytozoon bieneusi in Beef Cattle in Shanxi Province, North China - Ya-Ya Liu; Rui-Lin Qin; Jin-Jin Mei; Yang Zou; Zhen-Huan Zhang; Wen-Bin Zheng; Qing Liu; Xing-Quan Zhu; Wen-Wei Gao; Shi-Chen Xie (Animals, 2022)
Enterocytozoon bieneusi is an intracellular pathogen that can parasitize humans and a variety of animals. The infection of E. bieneusi in most hosts is asymptomatic, but in immunocompromised individuals, it can lead to serious complications such as acute diarrhea, dehydration, and even death. However, no data on the prevalence and genotyping of E. bieneusi in beef cattle in Shanxi province are currently available. In this study, a total of 401 fecal samples were collected from beef cattle in farms from two representative counties—Qi county and Jishan county—in Shanxi province, north China. Nested PCR was applied to determine the prevalence and genotypes of E. bieneusi by amplifying and sequencing the internal transcribed spacer (ITS) regions of the rRNA gene. A total of 90 out of 401 samples were detected as E. bieneusi-positive, with 22.44% overall prevalence of E. bieneusi in beef cattle in Shanxi province. The highest prevalence of E. bieneusi was detected in calves (28.67%, 41/143) and male beef cattle (28.13%, 54/192). Statistical analysis revealed that the prevalence of E. bieneusi was significantly associated with gender and age factors (p < 0.05), but without any statistical difference among regions. Moreover, six known E. bieneusi genotypes (BEB4, BEB6, BEB8, J, I, and PigSpEb2) and two novel genotypes (designated CSC1 and CSC2) were identified by analysis of ITS sequences, and genotype I was the predominant genotype in these two counties. Phylogenetic analysis showed that five known genotypes and two novel genotypes were clustered into Group 2, but PigSpEb2 belonged to Group 1. To our knowledge, the present study demonstrated the presence and identified genotypes of E. bieneusi in beef cattle in Shanxi province for the first time, extending the data on prevalence and genotypes of E. bieneusi in beef cattle and providing baseline data for executing intervention measures to control it in the study regions.